Team Games Tournament (TGT) as an Innovative Pedagogical Strategy in Economics Education: A Literature-Based Analysis - Meri Elvionita; Armiati Armiati (Nurul Jadid University, 2025)
The development of digital technology has shifted the learning paradigm towards a more interactive and collaborative approach. This study aims to evaluate the effectiveness of the Team Games Tournament (TGT) learning model combined with Baamboozle media in improving the quality of the process and student learning outcomes. The research method used was a Systematic Literature Review (SLR) and bibliometric analysis of articles retrieved from Google Scholar in the 2020–2025 period. From the search results, 10 publications relevant to the research topic were obtained. The results of the study indicate that the implementation of the TGT model assisted by Baamboozle can improve students' learning outcomes, motivation, active participation, teamwork, and critical thinking skills. In addition, the bibliometric analysis shows that dominant keywords such as